The Use of AI Illustration Media to Improve Critical Thinking Skills in Pancasila Education Learning - Kiki Muhamad Lutfi; Dasim Budimansyah; Dede Iswandi (FKIP - Universitas Riau, 2026)
This study aims to determine the impact of using Artificial Intelligence (AI)-based illustration media on the critical thinking skills regarding civic values within Pancasila Education instruction. A quasi-experimental method with a non-equivalent control group design was employed. The research subjects consisted of 24 students in the experimental class (Class XI F2) and 32 students in the control class (Class XI F1) at SMA PGRI 2 Bandung. The experimental class utilized AI-based illustration media within a Project-Based Learning (PjBL) framework, whereas the control class did not use AI illustrations. Data analysis involved Mann-Whitney, Wilcoxon, and N-Gain tests. The results indicate that the experimental class experienced an improvement in critical thinking skills; the average score for the experimental class rose from 67.8 to 81.7, while the control class saw a slight increase from 65.2 to 67.7. The Mann-Whitney test results on N-Gain scores revealed a significant difference in improvement between the two groups (p < 0.001). Questionnaire results also demonstrated a generally positive student response to the use of AI illustration media. Based on these findings, the use of PjBL-based AI illustration media has a statistically significant impact on students' critical thinking skills and holds the potential to foster more active, interactive, and engaging learning experiences in Pancasila Education.